Using Plastic Mulching Improves Greenhouse-Grown Pakchoi (Brassica rapa subsp. chinensis) Growth and Water Use Efficiency under Irrigation Scheduling Based on Soil Water Content - Yue Xie; Shenglin Wang; Chen Luo; Mengyao Sun; Yixin Wang; Jingjing Yang; Qian Wang (Agronomy, 2020)
Scarce water resources limit protected vegetable production in North China. Implementing efficient water-saving techniques is crucial for maintaining protected vegetable production and sustainability. A two-growing season field experiment was conducted in a glass greenhouse to explore the effects of water-saving techniques with irrigation scheduling based on soil water content on the growth and quality of pakchoi and the fate of irrigation water. Three water-saving techniques were investigated: micro-irrigation (M-0), furrow irrigation with plastic mulch (F-P), and micro-irrigation with plastic mulch (M-P) compared to furrow irrigation (F-0). F-P and M-P treatments enhanced pakchoi growth and primarily increased the total root length of the root system (0–0.2 m) compared to F-0. The two treatments further induced an improvement of pakchoi quality. Compared to M-0, F-P and M-P treatments showed better performance in reducing evaporation by 57–70% and proportion of evaporation in evapotranspiration, and consequently exhibited more pronounced effects on water saving. Irrigation water use efficiency (IWUE) was improved in F-P by 50% in both seasons and was improved in M-P by 84 and 95% in spring season and autumn season, respectively. Combining irrigation scheduling based on soil water content with plastic mulch is a feasible way to improve IWUE in protected vegetable production by reducing water consumption and enhancing crop growth.